(untitled) (Journal of the College of Basic Education, 2026)
The theatrical performance is a visual discourse consisting of a semiotic network that includes visual and auditory elements of the performance as intertwined semantic patterns that are read by the recipient through an agreed-upon collective cultural communication language. The mask constitutes one of these semantic patterns, which includes internal signs that are organized as symbols within a network of the performance (lines, shapes, materials, colors, etc.). The symbol is a semiotic system that allows the transfer of information from a sender to a receiver within a semiotic structure that Peirce described as operating on three levels (icon, sign, and symbol). Given the importance of the mask in theatrical performances, the researcher formulated the title of her research: (The mask as a symbolic discourse in the costumes of theatrical performances). This leads us to question the nature of the mask and its role in performances, considering it as a symbolic system within the costume in the intricate structure of the performance. The importance of the research lies in enabling directors, authors, and scenographers to formulate, deconstruct, and interpret the symbols of the performance. The research aims to identify the internal elements of the mask and how it generates codes that serve the message of the performance. The researcher then defined the most important terms in the research, which are the mask, the symbol, and the symbolic discourse. Chapter Two, The Theoretical Framework, includes two sections, the first of which is (Symbolic Discourse in the Theatrical Mask). As a sample for her research, the researcher employed a purposive method to suit the research requirements. She utilized several tools to collect data and information, including documents, books, letters and dissertations, photographs, and films. Among the most important conclusions reached were that the mask can be replaced by heavy makeup or a costume that carries the connotations of the mask. The mask functions as a symbolic and referential system in contemporary theatrical performances, as contemporary theater has invoked the symbols of ancient civilizations due to their visual communication language, which aligns with the philosophy of current societies, thus achieving a wealth of meaning. As in the Egyptian and Asian civilizations, which used color coding and shape coding as cultural symbols agreed upon in their societies, the researcher also focused on formulating recommendations, which is the necessity of paying attention to the study of the mask as it forms an integrated semantic system within the theatrical performance and not dealing with it as an aesthetic element, due to its ability to produce a multi-level symbolic discourse.